2019
DOI: 10.1172/jci.insight.129212
|View full text |Cite
|
Sign up to set email alerts
|

Cellular heterogeneity during mouse pancreatic ductal adenocarcinoma progression at single-cell resolution

Abstract: fibroblasts (CAFs). These data will provide a resource for future studies aimed at further characterizing and targeting specific cell populations in PDA. ResultsCellular heterogeneity during PDA progression. We sought to determine the composition of single cells during the progression of PDA GEMMs. Normal mouse pancreas; 40-day-old Kras LSL−G12D/+ Ink4a fl/fl Ptf1a Cre/+ (KIC) (5) mouse pancreas, termed "early KIC" (with the early lesion initially confirmed by ultrasound; Supplemental Figure 1; supplemental ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
157
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(182 citation statements)
references
References 51 publications
15
157
0
Order By: Relevance
“…Furthermore, we found that CAFs are a major source of TGFβ‐induced IL‐6 expression. Several recent studies including ours demonstrate the existence of fibroblast heterogeneity within PDA (Ohlund et al , ; Bernard et al , ; Elyada et al , ; Hosein et al , ). Two major populations of CAFs have been identified, one is characterized by an inflammatory feature, while the other has been known as myofibroblast.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Furthermore, we found that CAFs are a major source of TGFβ‐induced IL‐6 expression. Several recent studies including ours demonstrate the existence of fibroblast heterogeneity within PDA (Ohlund et al , ; Bernard et al , ; Elyada et al , ; Hosein et al , ). Two major populations of CAFs have been identified, one is characterized by an inflammatory feature, while the other has been known as myofibroblast.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, several studies, including ours, suggest the existence of two different subtypes of CAFs in PDA (Ohlund et al , ; Bernard et al , ; Elyada et al , ; Hosein et al , ). Of the two CAF populations, one appears to be inflammatory, characterized by PDGFRα expression and the secretion of a variety of inflammatory chemokines.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…In breast tumors, four subset of CAFs were captured in MMTV‐PyMT tumors, namely vascular CAFs (vCAF), matrix CAFs (mCAF), cycling CAFs (cCAF), and developmental CAFs (dCAF), representing a perivascular origin (vCAF and cCAF), a resident fibroblast origin (mCAF), and an EMT origin (dCAF) . In pancreatic cancer in contrast to normal pancreas, distinct CAFs subpopulations include a population associated with insulin‐like growth factor signaling (FB1), a population expressing Ly6a/c1 (lymphocyte antigen complex locus and locus c1) and Pi16 (peptidase inhibitor 16) (FB2), and a population with mesothelial markers, including Msln (mesothelin), and Cav1 , Cdh11 (cadherin 11), and Gas6 (growth arrest‐specific 6) (FB3) . Interestingly, only FB1 and FB3 persisted in pancreatic ductal adenocarcinoma (PDAC), with FB2 cells merging toward an FB1 transcriptome, and FB3 contain Acta2 + myofibroblasts as well as MHCII + cells, suggesting an immune modulatory function.…”
Section: Single‐cell Resolution Of Fibroblastsmentioning
confidence: 99%